2022
DOI: 10.1038/s42003-022-03495-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced inhibin promotes tumor growth and vascular permeability in ovarian cancers

Abstract: Hypoxia, a driver of tumor growth and metastasis, regulates angiogenic pathways that are targets for vessel normalization and ovarian cancer management. However, toxicities and resistance to anti-angiogenics can limit their use making identification of new targets vital. Inhibin, a heteromeric TGFβ ligand, is a contextual regulator of tumor progression acting as an early tumor suppressor, yet also an established biomarker for ovarian cancers. Here, we find that hypoxia increases inhibin levels in ovarian cance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 77 publications
3
7
0
Order By: Relevance
“…Inhibins belong to the TGF-beta family and is comprised of a functional heterodimer with an alpha- and a beta-subunit. Inhibin promotes angiogenesis through TGF-beta receptors (116) and increases vascular permeability through internalization of VE-cadherin (117). Under hypoxic conditions, Inhibin expression is modulated HIF-1a and HIF-2a (118).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibins belong to the TGF-beta family and is comprised of a functional heterodimer with an alpha- and a beta-subunit. Inhibin promotes angiogenesis through TGF-beta receptors (116) and increases vascular permeability through internalization of VE-cadherin (117). Under hypoxic conditions, Inhibin expression is modulated HIF-1a and HIF-2a (118).…”
Section: Discussionmentioning
confidence: 99%
“…Within 12 hours, CA-MSCs and TCs readily formed tunneling nanotubes (TNTs), suggesting that physical contact via TNTs is a significant interaction between CA-MSCs and TCs (Fig 2A). Previous studies have shown that MSCs use TNTs to donate mitochondria to adjacent cells in times of ischemic and metabolic stress 20,21,22,23,25 , which are similar conditions to the hypoxemia and nutrient scarcity of the ovarian tumor microenvironment [24][25][26][27][28][29][30][31][32][33][34][35][36] . To investigate if CA-MSCs donate mitochondria to adjacent ovarian tumor cells via physical interaction, we repeated the IncuCyte experiment along with a red actin stain to highlight TNT formation.…”
Section: Ca-mscs Transfer Mitochondria To Adjacent Tumor Cellsmentioning
confidence: 99%
“…We found that TCs cocultured 1:1 with CA-MSCs under non-adherent conditions exhibited a two-to-four-fold increase in mitochondrial transfer compared to cocultures in standard adherent conditions (Fig2D). Given that MSCs have been shown to donate mitochondria under ischemic stress to cardiomyocytes 20,21,22,23 and that the ovarian tumor microenvironment is hypoxic [24][25][26][27][28][29][30][31][32][33][34][35][36] , we also tested if hypoxia influenced CA-MSC mitochondrial transfer. CA-MSCs and TCs were grown under non-adherent conditions in normoxic (21% O2) or hypoxic (1% O2) conditions.…”
Section: Ca-mscs Transfer Mitochondria To Adjacent Tumor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mythreye Karthikeyan (Pathology & Comprehensive Cancer Center, University of Alabama, Birmingham) shared data on the role of the Activin subfamily Inhibin proteins in ovarian cancer 7 . Inhibins are either homodimers or heterodimers comprising various combinations of Inhibin-α, Inhibin-βA (InhibinA), or Inhibin-βB (InhibinB) subunits.…”
Section: Introductionmentioning
confidence: 99%